2019
DOI: 10.1891/0886-6708.34.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Does Training and Coursework in Domestic Violence Affect Students' Perceptions of Behaviors as Domestic Violence?

Abstract: Some argue that training and/or coursework in domestic violence (DV) could impact the beliefs criminal justice (CJ) majors have about DV and, in turn, affect their future job performance in cases involving victims of DV. This study examined the association of previous education and training in DV on the beliefs college students hold about what behaviors qualify as DV. Further, it examined the association between CJ versus non-CJ majors on beliefs about DV behaviors. Results indicated prior education on DV, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Allen-Ebrahimian ( 62 ) reported that China witnessed a three-fold increase in the cases of domestic violence after imposing quarantine. Different states in the United States also reported an increase of about 21–35% in domestic violence ( 63 ). Even the UK has been facing concerns due to rising family violence.…”
Section: Covid-19 and Gender Violencementioning
confidence: 99%
“…Allen-Ebrahimian ( 62 ) reported that China witnessed a three-fold increase in the cases of domestic violence after imposing quarantine. Different states in the United States also reported an increase of about 21–35% in domestic violence ( 63 ). Even the UK has been facing concerns due to rising family violence.…”
Section: Covid-19 and Gender Violencementioning
confidence: 99%
“…Allen-Ebrahimian (2020) reported that China witnessed a threefold increase in domestic violence cases after imposing lockdown. Different states in the United States also reported about 21–35% increase in the number of domestic violence recorded ( Wagers, 2020 ). According to Bradbury-Jones and Isham (2020) , the lockdown imposed to deal with COVID-19 pandemic has granted greater freedom to abusers.…”
Section: Introductionmentioning
confidence: 99%